Investing in pastoralism: ILRI speaks with CNBC Africa - Mude, Andrew G. (CNBC Africa, 2011)
ILRI’s Andrew Mude interviewed live on DSTV television on August 24, 2011 by a South African journalist on the drought in the Horn, what can be done to enhance pastoral resilience in this region in the face of recurring droughts, such as his project that is insuring pastoral livestock against drought for the first time.